2020
DOI: 10.3390/nu12092573
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral, Anti-Inflammatory Effects of Natural Medicinal Herbs and Mushrooms and SARS-CoV-2 Infection

Abstract: The 2019 novel coronavirus, SARS-CoV-2, producing the disease COVID-19 is a pathogenic virus that targets mostly the human respiratory system and also other organs. SARS-CoV-2 is a new strain that has not been previously identified in humans, however there have been previous outbreaks of different versions of the beta coronavirus including severe acute respiratory syndrome (SARS-CoV1) from 2002 to 2003 and the most recent Middle East respiratory syndrome (MERS-CoV) which was first identified in 2012. All of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 63 publications
1
64
0
1
Order By: Relevance
“…Currently, there are relatively few studies on the antiviral mechanism of Inonotus obliquus , and further research is needed. It was reported that IOPS could inhibit the induction of NO and other similar cytokines, a phenomenon that had been associated with Covid-19 [ 132 , 133 ]. By using cell models of feline calicivirus (FCV) in vitro, Tian revealed the mechanism of IOPS treatment was that it might induce its inhibitory actions directly on virus particles through blocking viral binding/absorbing, and this demonstrated that IOPS might be a potential broad-spectrum antiviral drug against feline viruses [ 134 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…Currently, there are relatively few studies on the antiviral mechanism of Inonotus obliquus , and further research is needed. It was reported that IOPS could inhibit the induction of NO and other similar cytokines, a phenomenon that had been associated with Covid-19 [ 132 , 133 ]. By using cell models of feline calicivirus (FCV) in vitro, Tian revealed the mechanism of IOPS treatment was that it might induce its inhibitory actions directly on virus particles through blocking viral binding/absorbing, and this demonstrated that IOPS might be a potential broad-spectrum antiviral drug against feline viruses [ 134 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…Saikosaponin-A, -B2, C and D have been reported to induce substantial antiviral effects against HCoV-22E9 [ 63 ]. These are the naturally occurring triterpene glycosides found and extracted from a number of medicinal plants including Scrophularia scorodonia, Heteromorpha spp.…”
Section: Natural Products With Promising Antiviral Potential Against Coronavirusesmentioning
confidence: 99%
“…Significance of uptake of mushrooms has been raised now more than ever during the pandemic SARS-CoV-2 because there is no specific treatment or vaccine is available to fight against it but by the regular intake of natural products like Inonotus obliquus, lentinula edodes, and Grifola frondosa with effective antiviral and anti-inflammatory peculiarities, effects of SARS-CoV-2 can be minimized (Shahzad et al 2020). The main aim of this review is to describe different aspects of medicinal and edible mushroom by which it has revolutionized the world; a step toward the nongreen revolution.…”
Section: Introductionmentioning
confidence: 99%